The Role of Tricarboxylic Acid Cycle Metabolites in Viral Infections - Sánchez-García, Francisco Javier; Pérez-Hernández, Celia Angélica; Rodríguez-Murillo, Miguel; Moreno-Altamirano, María Maximina Bertha (Frontiers in Cellular and Infection Microbiology, 2021)
Host cell metabolism is essential for the viral replication cycle and, therefore, for productive infection. Energy (ATP) is required for the receptor-mediated attachment of viral particles to susceptible cells and for their entry into the cytoplasm. Host cells must synthetize an array of biomolecules and engage in intracellular trafficking processes to enable viruses to complete their replication cycle. The tricarboxylic acid (TCA) cycle plays a central role in ATP production as well as in the synthesis of the biomolecules required for viral replication. The final assembly and budding process of enveloped viruses, for instance, require lipids, and the TCA cycle provides the precursor (citrate) for fatty acid synthesis (FAS). Viral infections may induce host inflammation and TCA cycle metabolic intermediates participate in this process, notably citrate and succinate. On the other hand, viral infections may promote the synthesis of itaconate from TCA cis-aconitate. Itaconate harbors anti-inflammatory, antioxidant, and anti-microbial properties. Fumarate is another TCA cycle intermediate with immunoregulatory properties, and its derivatives such as dimethyl fumarate (DMF) are therapeutic candidates for the contention of virus-induced hyper-inflammation and oxidative stress. The TCA cycle is at the core of viral infection and replication as well as viral pathogenesis and anti-viral immunity. This review highlights the role of the TCA cycle in viral infections and explores recent advances in the fast-moving field of virometabolism.